Modern Literature and Christianity: The Religious Issue in Lucien Rebatet's Les Deux étendards - Pascal A. Ifri (Studies in 20th & 21st Century Literature, 2001)
Although Lucien Rebatet's Les Deux étendards (The Two Standards) has been hailed by a number of critics as one of the best novels written in France since World War II, it is surrounded by a wall of silence because its author actively supported the Nazi movement before and during the war. Yet the novel does not deal with politics but with love, art, and religion. Based on real events, it is the story of a love triangle involving Michel, who has lost his Catholic faith, Régis, who studies to become a Jesuit priest, and Anne-Marie, a young student who shares a mystical love with Régis and also intends to join a religious order. When Michel meets Anne-Marie, he falls desperately in love with her, but hopelessly since she belongs to God and to Régis. Yet, fascinated by his friends' adventure, he tries to recover the faith he has lost in order to join them on their mystical plane, but eventually fails. The theme of religion and more specifically Catholicism dominates Les Deux étendards which treats the most complex religious issues with passion and intensity and tackles the history of the Church and religious exegesis with a thoroughness and a minuteness worthy of Proust. Over one thousand pages, Les Deux étendards, mainly through Régis and Michel's animated discussions, reenacts the quarrel that has been raging for two thousand years between believers and nonbelievers. If, in the end, Les Deux étendards condemns religion, it is in order to better affirm what can be called the sacred or the spiritual which stands in opposition to the religious. In any case, this passionate handling of religion, its place at the heart of the story and its intimate association with the other main themes, love and art, largely account for the originality of the novel.
Keywords: Lucien Rebatet; Les Deux étendards; The Two Standards; France; Nazi; support Nazi; love; art; religion; Michel; Catholic; Catholic faith; Régis; Jesuit Priest; Anne-Marie; student; mystical love; God; history of the Church; religious exegesis; Proust; spiritual; original